EVALUASI KINERJA KEUANGAN KOPERASI DARI ASPEK EFEKTIVITAS BERDASARKAN PEDOMAN PEMERINTAH STUDI KASUS KSU PERWIRA PURBALINGGA - Aprilia, Dwiani Nursasi; Arruum, Cintia; Nuristiyanti, Nia; Wiratno, Adi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
This study aims to determine the Financial Performance of PERWIRA Purbalingga's Multi-Business Cooperative (KSU) from a productivity aspect according to Government guidelines in the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/M.KUKM/V/2006. Data collection was carried out through interviews with cooperative management. collect data such as balance sheets, income statements, the history of the establishment of the cooperative, organizational structure, and the articles of association and bylaws of the cooperative. in terms of the development of profitability, Return on Assets, Asset Turn Over (ATO), Net Profit Margin, and total debt to own capital at KSU